Asymptotic Behavior of Solutions of Linear Singularly Perturbed General Separated Boundary-Value Problems with Initial Jump - Kasymov, K. A.; Nurgabyl, D. N. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We obtain asymptotic estimates for solutions of singularly perturbed boundary-value problems with initial jumps.